Association between daily maximum temperature and immediate-to-delayed gout flare hospitalisations: a population-level time series study in metropolitan Perth, Australia - Lopez, Derrick; Marriott, Ross J.; Nossent, Johannes; Keen, Helen I.; Inderjeeth, Charles; Preen, David B. (International Journal of Population Data Science, 2026)
Background Ambient temperature may alter the risk of gout flare. We assessed the association between daily maximum temperature on the immediate-to-delayed (lag) hospitalisations for gout flare at the whole-population-level. Methods Data were extracted from the Western Australian Hospital Morbidity Data Collection for this time series study for metropolitan Perth (Australia) from 1980-2014, with meteorological data obtained from the Scientific Information for Land Owners dataset. We examined the association (relative risk [RR] and 95% confidence intervals [CI]) between hospitalisation for gout flare, daily maximum temperature and lag days since exposure using quasi-Poisson regression and the distributed lag non-linear model. Results Average daily maximum temperature was 24°C (5th percentile=17°C; 95th percentile=36°C). Maximum temperatures of 17°C and 36°C were associated with 6.2 and 6.8 gout admissions per 1,000,000 population over lag day 0 to lag day 21 following exposure, respectively. Risk of hospitalisation for gout (reference=24°C) with maximum temperature was modified by age and sex. Males aged ≥75 years had higher risks of gout hospitalisation following hotter days (36°C) beginning immediately on lag day 0 (RR=1.39; 95% CI: 1.02-1.88) and from lag day 7 (RR=1.11; 95% CI: 1.01-1.21) to lag day 10 after colder days (≤15°C). Females aged ≥75 years had higher risk at 35°C from lag day 3 (RR=1.12; 95% CI: 1.02-1.23) to lag day 4. Males aged <75 years had higher risks after 35°C days from lag day 6 (RR=1.06; 95% CI: 1.01-1.12) to lag Day 8 but lower risk from lag day 7 (RR=0.96: 95% CI: 0.92-0.99) to lag day 8 following colder days (17°C). Conclusion Our study shows associations between extreme temperatures, both hot and cold, and immediate-to-delayed gout flare hospitalisations. Our findings will inform and guide public health measures and health system preparedness during the impending extremes of temperature with particular attention to older people.